Advanced MR diffusion imaging and chemotherapy‐related changes in cerebral white matter microstructure of survivors of childhood bone and soft tissue sarcoma?. Issue 8 (20th April 2018) - Sleurs, Charlotte; Lemiere, Jurgen; Christiaens, Daan; Billiet, Thibo; Peeters, Ronald; Sunaert, Stefan; Uyttebroeck, Anne; Deprez, Sabine
Abstract: With the increase of survival rates of pediatric cancer patients, the number of children facing potential cognitive sequelae has grown. Previous adult studies suggest that white matter (WM) microstructural changes may contribute to cognitive impairment. This study aims to investigate WM microstructure in childhood bone and soft tissue sarcoma. Differences in (micro‐)structure can be investigated using diffusion MRI (dMRI). The typically used diffusion tensor model (DTI) assumes Gaussian diffusion, and lacks information about fiber populations. In this study, we compare WM structure of childhood bone and soft tissue sarcoma survivors ( n = 34) and matched controls ( n = 34), combining typical and advanced voxel‐based models (DTI and NODDI model, respectively), as well as recently developed fixel‐based models (for estimations of intra‐voxel differences, apparent fiber density [AFD] and fiber cross‐section [FC]). Parameters with significant findings were compared between treatments, and correlated with subscales of the WAIS‐IV intelligence test, age at diagnosis, age at assessment and time since diagnosis. We encountered extensive regions showing lower fractional anisotropy, overlapping with both significant NODDI parameters and fixel‐based parameters. In contrast to these diffuse differences, the fixel‐based measure of AFD was reduced in the cingulum and corpus callosum only. Furthermore, AFD of the corpus callosum was significantly predicted by chemotherapy treatment and correlated positively with time since diagnosis, visual puzzles and similarities task scores. This study suggests altered WM structure of childhood bone and soft tissue sarcoma survivors. We conclude global chemotherapy‐related changes, with particular vulnerability of centrally located WM bundles. Finally, such differences could potentially recover after treatment.